Development of Nutrient Control System in Plant Factory based on Growth Phases of Romaine Lettuce (Lactuca sativa var. longifolia) - Rozaaq, Naufal Ilhamdi; Eka Putri, Renny; Yanti, Delvi (Journal of Tropical Agricultural Engineering and Biosystems - Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2024)
Nutrient is one of the conditions controlled in a plant factory. Nutrient control must be based on the plant growth phase, but previous research has shown shortcomings in this area. This study aims to develop a nutrient control system in a plant factory based on the plant growth phase, specifically using Romaine lettuce. The research method used is the experimental method, with research stages including system design (controller modification, programming, and TDS sensor calibration testing) and system performance testing. The TDS sensor calibration test results showed an R² of 0.9999, indicating that the TDS sensor readings are very close to those of the TDS meter. The system performance test results showed that the developed system works well in controlling nutrient levels based on the growth phase of Romaine lettuce. The planting process lasted 30 days, from October 13, 2023, to November 11, 2023, with a total of 2,697 data points recorded by Antares. Nutrient requirements were adjusted per the growth phase of Romaine lettuce, with set points in the first to fourth weeks being 500 PPM, 600 PPM, 700 PPM, and 800 PPM, respectively. The average nutrient levels recorded in the first week were 518 PPM, 623 PPM in the second week, 721 PPM in the third week, and 820 PPM in the fourth week. The TDS sensor accuracy test results showed an R² of 0.9998, indicating that the TDS sensor performed well in controlling nutrient levels during the system testing, with an average TDS sensor reading error of only 1.17%. During the planting process, the total amount of nutrients added for each of nutrients A and B was 210.10 ml, with the total operating time of the control components being 314.34 seconds for each peristaltic pump of nutrients A and B.